2019
DOI: 10.1177/1550147719894533
|View full text |Cite
|
Sign up to set email alerts
|

Region of interest–based segmented tiled adaptive streaming using head-mounted display tracking sensing data

Abstract: To support 360 virtual reality video streaming services, high resolutions of over 8K and network streaming technology that guarantees consistent quality of service are required. To this end, we propose 360 virtual reality video player technology and a streaming protocol based on MPEG Dynamic Adaptive Streaming over HTTP Spatial Representation Description to support the player. The player renders the downsized video as the base layer, which has a quarter of the resolution of the original video, and high-quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Even with the advance of deep learning methods in which the latent features are learned automatically, these features still lack the ability to generate rich semantic explanations, especially with streaming data. On the other hand, lightweight models (Kim & Yang, 2019) rely on threshold-based predicates over spectral indexes, which are somewhat understandable for domain experts. However, they often yield a lower prediction power in practice.…”
Section: Explainable Systemsmentioning
confidence: 99%
“…Even with the advance of deep learning methods in which the latent features are learned automatically, these features still lack the ability to generate rich semantic explanations, especially with streaming data. On the other hand, lightweight models (Kim & Yang, 2019) rely on threshold-based predicates over spectral indexes, which are somewhat understandable for domain experts. However, they often yield a lower prediction power in practice.…”
Section: Explainable Systemsmentioning
confidence: 99%
“…The authors showed that differentiated quality streaming results in a bandwidth saving of 72% in comparison to a baseline approach. Kim and Yang [123] used an enhanced version of MPEG-DASH SRD to choose between quality variable tile layers. The researchers designed 15 https://github.com/tnomedialab/dash-srd.js and implemented a multilayer rendering enabled 360 • VR player based on their previous work [124] to support highresolution and low latency streaming for highly unpredictable head motion data.…”
Section: Tile-based Streamingmentioning
confidence: 99%